2015
DOI: 10.1215/00127094-2871306
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Clifford–Severi inequality and the volume of irregular varieties

Abstract: We give a sharp lower bound for the self-intersection of a nef line bundle L on an irregular variety X in terms of its continuous global sections and the Albanese dimension of X, which we call the Generalized Clifford-Severi inequality. We also extend the result to nef vector bundles and give a slope inequality for fibred irregular varieties. As a byproduct we obtain a lower bound for the volume of irregular varieties; when X is of maximal Albanese dimension the bound is vol(X) ≥ 2 n! χ(ωX) and it is sharp.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Let us first recall the classical results, which are due mainly to Castelnuovo: see [1,Chapter III,§ 2]. Let C be a smooth curve and consider a subspace W ⊆ H 0 (C, L) of dimension r + 1 2 such that the moving part of |W | is a base point free g r d (hence deg L d).…”
Section: Continuous Castelnuovo Inequalitiesmentioning
confidence: 99%
“…Let us first recall the classical results, which are due mainly to Castelnuovo: see [1,Chapter III,§ 2]. Let C be a smooth curve and consider a subspace W ⊆ H 0 (C, L) of dimension r + 1 2 such that the moving part of |W | is a base point free g r d (hence deg L d).…”
Section: Continuous Castelnuovo Inequalitiesmentioning
confidence: 99%
“…In particular, h 0 alb S (S, K S ) = χ(S). In [2] the following Severi-type inequalities are proved (see [2] for a much more complete statement).…”
Section: 2mentioning
confidence: 99%
“…Theorem 2.6 (Barja, [2]). Let S be a smooth surface with a generating morphism a : S → A to an abelian variety A; suppose that S is of maximal a-dimension and L is a nef divisor on S. Then (i) The following inequality holds:…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In another very recent paper, Hu [23] showed that K 3 X ≥ 4 3 χ(ω X ) − 2 in this case. Also, the author has been informed by Miguel Barja that in [2,Remark 4.6], the first inequality of Theorem 1.3 is also independently proved by him using a different method.…”
Section: Introductionmentioning
confidence: 99%